THE PLOT DECOMPOSITION OF THE BATMAN MOVIE BY MATT REEVES (Journal of English Language Teaching Development, 2024)
The study aimed to describe the plot decomposition and character characterization of Matt Reeves's movie of The Batman. The plot of the movie depicted the first two years of the night that transformed Bruce Wayne into a nocturnal animal. But as he continued to find his way to becoming Gotham's Dark Knight, Bruce had been forced into a cat-and-mouse game with his greatest threat yet, a crazed killer known for his name “The Riddler”, who was filled with rage and determination to expose the corrupt system. while casting all of Gotham's key political figures. Bruce had to track down the killer and brought him to justice, while also questioning his influence on Gotham up until The Batman. The study investigated the plot of a movie based on an analysis of the movie Batman. The final study was aimed at using a descriptive-qualitative research. The results showed that the plot line was classified as a mixed line, with plot characteristics showing character transformations when faced with moral dilemmas.